Effects of Physical Exercise on Oxidative Stress Biomarkers in Hypertensive Animals and Non-Diabetic Subjects with Prehypertension/Hypertension: A Review - Cofre-Bolados, C; Poblete-Aro, C (Springer-Verlag Italia s.r.l., 2019)
Background: Oxidative stress (OS) is a condition that alters different functions of the organism inducing high blood pressure (HBP). Although physical exercise is recommended for the treatment of HBP, it is not clear which exercise method is more efficient to reduce OS biomarkers in subjects with HBP and non-type 2 diabetes mellitus (T2DM). Therefore, this review aimed to determine the effect of physical exercise on the OS biomarkers of HBP animal models and non-T2DM prehypertensive/hypertensive human adults. Methodology: An online search was done in WoS, Scopus and PubMed (MeSH) databases with the following combination of keywords: “hypertension” AND “oxidative stress” AND “exercise”. Results: A total of 1128 articles were identified, from which only six articles on animal research and six on human research fulfilled the inclusion and exclusion criteria. In animal models, exercise reduced OS biomarkers and decreased systolic blood pressure. In humans, five of these articles showed a significant decrease in OS biomarkers along with a decrease in systolic blood pressure (SBP) and diastolic blood pressure (DBP) and a single study found an increase in OS biomarkers co-occurring with a decrease in SBP/DBP. Conclusions: Based on the analyzed articles, it is concluded that physical exercise, in its different modalities, allows the reduction of OS biomarkers, together with a significant decrease in SBP/DBP. Moderate intensity aerobic exercise presents a higher body of evidence compared to resistance training and flexibility training. For this reason, it is recommended to conduct more randomized clinical trials with these last two methods. © 2019, Springer-Verlag Italia S.r.l., part of Springer Nature.